2016
DOI: 10.1590/s1518-8787.2016050006595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neighborhood socioeconomic status on blood pressure in older adults

Abstract: OBJECTIVE To test if the neighborhood socioeconomic status is associated with systolic blood pressure and hypertension in older adults.METHODS A cross-sectional population-based study with a sample of 1,705 older adults from Florianópolis, SC, Southern Brazil. The contextual variable used was the average years of schooling of the head of the household in census tracts. Participants were considered hypertensive when the systolic blood pressure was ≥ 140 mmHg, diastolic ≥ 90 mmHg, or both. Additionally, the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…However, rural dwellers use more traditional than the orthodox hypertension management techniques as shown by 100% of the respondents who take adequate intake of a balanced diet. The result aligns with the findings of [47] as they reported that most respondents understood that hypertension can be managed by the use of both traditional and orthodox techniques. ed information through media and educational institutions.…”
Section: Usage Of Various Hypertension Management Techniquessupporting
confidence: 86%
“…However, rural dwellers use more traditional than the orthodox hypertension management techniques as shown by 100% of the respondents who take adequate intake of a balanced diet. The result aligns with the findings of [47] as they reported that most respondents understood that hypertension can be managed by the use of both traditional and orthodox techniques. ed information through media and educational institutions.…”
Section: Usage Of Various Hypertension Management Techniquessupporting
confidence: 86%
“…Individuals lacking in higher education are more likely to have hypertension, along with uncontrolled blood pressure values (Matei et al, 2018). Related work also shows that neighborhood socioeconomic status is related to systolic blood pressure among older individuals (Wagner, Boing, Subramanian, Hofelmann, & D'Orsi, 2016). Specifically, systolic blood pressure was significantly higher among individuals residing in census tracts with lower levels of education.…”
Section: Introductionmentioning
confidence: 99%
“…In general, education tends to present a positive association with better health outcomes. A study carried out in the city of Florianópolis showed that the low educational level is associated with increased SBP and increased odds of hypertension among older people [37]. The hypothesis is that individuals with higher educational levels are more knowledgeable about health and, thus, seek healthcare services more often.…”
Section: Discussionmentioning
confidence: 99%